2005
DOI: 10.1177/152692480501500213
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and Liver Living Donors: A Comparison of Experiences

Abstract: Donors in both groups reported favorable outcomes. A greater concern for risk of death, bleeding, altered appearance, and infection existed among liver donors compared to kidney donors. The actual outcomes were better than the perceived risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Studies were from 19 countries; most were conducted in the United States (43% of studies) followed by Germany (10%), Canada (6%), India (4%), Sweden (4%), Australia (4%), the Netherlands (4%) and Switzerland (4%). During follow-up, 46 studies assessed the physical health of donors (29)(30)(31)(32)(33)(34)(35)(36)38,(40)(41)(42)(43)(44)(45)(46)(48)(49)(50)(51)(53)(54)(55)(56)(57)(58)(59)(60)(61)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79) and 26 reported that some donors had faced graft failure or recipient death (29,(31)(32)…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies were from 19 countries; most were conducted in the United States (43% of studies) followed by Germany (10%), Canada (6%), India (4%), Sweden (4%), Australia (4%), the Netherlands (4%) and Switzerland (4%). During follow-up, 46 studies assessed the physical health of donors (29)(30)(31)(32)(33)(34)(35)(36)38,(40)(41)(42)(43)(44)(45)(46)(48)(49)(50)(51)(53)(54)(55)(56)(57)(58)(59)(60)(61)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79) and 26 reported that some donors had faced graft failure or recipient death (29,(31)(32)…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The remaining studies contacted previous donors' months to years after nephrectomy, with 20 studies not reporting the average time since donation (29)(30)(31)(32)(33)36,39,41,47,49,55,59,66,(68)(69)(70)(73)(74)(75)(76). The number of donors considered for follow-up was often unreported and thus for some studies, the response rate could not be calculated (37,39,41,52,56,59,64,68,72 (40,44,46,48,50,60,62,63,65,73,78) and five compared their characteristics to responders (40,44,46,50,65).…”
Section: Psychosocial Health Of Live Kidney Donorsmentioning
confidence: 99%
See 3 more Smart Citations